Proceedings of the Genetic and Evolutionary Computation Conference 2016 2016
DOI: 10.1145/2908812.2908958
|View full text |Cite
|
Sign up to set email alerts
|

Automatically Designing More General Mutation Operators of Evolutionary Programming for Groups of Function Classes Using a Hyper-Heuristic

Abstract: In this study we use Genetic Programming (GP) as an offline hyper-heuristic to evolve a mutation operator for Evolutionary Programming. This is done using the Gaussian and uniform distributions as the terminal set, and arithmetic operators as the function set. The mutation operators are automatically designed for a specific function class. The contribution of this paper is to show that a GP can not only automatically design a mutation operator for Evolutionary Programming (EP) on functions generated from a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Hong et al [21] first demonstrated that GP could automatically construct random number generators which are typically used in EP. In a second paper, it was shown that ADMs could be trained on collections of functions classes, showing good performance across a broader range of functions [34], however a tradeoff between general training and specific performance was observed. This paper presents a study of the design of 23 ADMs, for 23 functions classes, and then tests each of the 23 ADMs on each of the function classes.…”
Section: Automated Design Using Hyper-heuristicsmentioning
confidence: 99%
“…Hong et al [21] first demonstrated that GP could automatically construct random number generators which are typically used in EP. In a second paper, it was shown that ADMs could be trained on collections of functions classes, showing good performance across a broader range of functions [34], however a tradeoff between general training and specific performance was observed. This paper presents a study of the design of 23 ADMs, for 23 functions classes, and then tests each of the 23 ADMs on each of the function classes.…”
Section: Automated Design Using Hyper-heuristicsmentioning
confidence: 99%
“…Genetic programming (GP) [1] is a branch of evolutionary computation that can generate computer programs, and is widely applied in numerous fields [2][3][4][5][6][7][8][9][10]. Evolutionary programming (EP) is a black-box optimiser and mutation is the only operator in EP.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers classify hyper-heuristics according to the feedback sources in the learning process: Online learning hyper-heuristics learn from a single instance of a problem; Offline learning hyper-heuristics learn from a set of training instances and generalise to unseen instances [18]. Both online [2][3][4][5] and offline hyper-heuristics [6][7][8][9][10] are applied to various research fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations